Implementasi Pembelajaran TIK di Kelas V MIs Sirojul Falah 01 Kec. Parung Bogor - Agus Suryana; Dede Hendro Gunawan; Eka purwaningsih; Rumiyati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The study aims to analyze and describe the implementation of ICT learning for grade V students at MIS Sirojul Falah Parung, Bogor. The qualitative descriptive approac used with interviews, and observations to collect the data. Then in analyzing using the Milles and Huberman model, namely data reduction, data presentation, data analysis, and drawing conclusions. The results of the study show that the implementation of ICT learning for grade V students at MIS SIROJUL FALAH Parung, Bogor Regency has three stages in learning, namely planning, implementation, evaluation and follow-up. The implementation of ICT learning at MIS SIROJUL FALAH Parung Bogor still has many shortcomings. First, in terms of subject names, it still uses the name of the ICT subject which should have been changed to Informatics. The two curriculums used still use KTSP which should be the Independent Curriculum and the RPP used is not in line with the curriculum used. Third, the scope of the material taught still has many shortcomings where the material taught still contains old material that has not changed and is still around ICT which should be ICT material in MI or elementary school that is taught must contain Science, technology and mathematics. Fourth, computer facilities are still insufficient to meet the learning needs of students.